Inside the International Student World: Challenges, Opportunities, and Imagined Communities - Kaya, Jean (Journal of International Students, 2020)
Substantial research emphasizes recruitment and retention of international students over their lived experiences. This qualitative study employed a sociocultural lens to explore five international graduate students’ lived experiences in the United States and their postgraduation plans. Findings suggest that international graduate students navigate a World that encompasses individual worlds that revolve around challenges, opportunities, and imagined communities. I draw on Gee’s (2014) notion of capitalizing a word normally written in lower case to make clear two differing connotations of the word “world.” I discuss implications for higher education host institutions and their offices of international education.